A interdependência dos controles internos e a dimensão humana: a influência dos controles no aprimoramento do capital intelectual - Domingues, Débora de Fátima (2016)
The internal control environment through the COSO methodology contributes to the organization seeking to mitigate its business risks and for this, establishes guidelines for the organization, senior management, leadership and employees. At the heart of the issue of the control environment, it is the intellectual capital that, in the condition of an intangible asset, is considered the age of the knowledge and information, the great differential of competitive advantage to achieve results. Referring to intellectual capital as a competitive differential, it is only considered if it manifests in the organizational environment the skills needed for this contribution to the organization. In this sense, this research aimed to conduct a study on Internal Controls in companies and the improvement and engagement of intellectual capital in the control environment. The data collection was done through a questionnaire sent by email using structured questionnaire with closed questions, which was applied to employees of large companies. During the processing and analysis of the result, the correlation matrix was performed, which consists of the existence or not of a correlation between variables, which in this work, refers to the COSO elements with the Intellectual Capital and the control environment and the Individual Competences. The results show the strong correlation between the blocks of questions, especially regarding the intelligent controls, those that attend to the mutations and uncertainties to which they are submitted to the current organizations and being respected and valued. Moreover, the environment promotes human competence in practice, aimed at constant improvements of the controls, justifying the interdependence of the control environment with the improvement of intellectual capital